PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DI KOTA JAYAPURA - Putri Aristantia, Manisya (Berajah Journal, 2025)
One of the crimes that has recently become increasingly common is sexual violence, which can occur in various levels of society. Sexual violence is any act that includes sexual harassment to the act of forcing someone to have sexual relations without the victim's consent or when the victim does not want it, and/or having sexual relations in ways that are not normal or that the victim does not like and distancing (isolating) them from their sexual needs. This type of research is empirical legal research, with a sociological legal approach that analyzes a situation that occurs in society. Factors that influence someone to commit acts of sexual violence against children in Jayapura City are family factors, education, environment and other factors. Legal protection for children who are victims of sexual violence reported to the Jayapura City Police generally uses Article 76D in conjunction with Article 81 paragraph (1) and Article 76E in conjunction with Article 82 paragraph (1) of the Child Protection Law.